East Asia imperilled : - Dupont, Alan (Cambridge University Press, 2001)
In this pathbreaking analysis, Alan Dupont argues that an emerging new class of non-military threats has the potential to destabilize East Asia and reverse decades of hard-won economic and social development. Transnational threats stem from overpopulation, deforestation and pollution, global warming, unregulated population movements, transnational crime and virulent new strains of infectious diseases. This authoritative book is essential reading for East Asia specialists and makes a significant and timely contribution to international security debates.